Physiological and biochemical mechanisms of allelopathy mediated by the allelochemical extracts of Phytolacca latbenia (Moq.) H. Walter. (October 2015) - Ullah, Nazif; Haq, Ihsan Ul; Safdar, Naila; Mirza, Bushra
In allelopathy, one plant suppresses the growth and development of other plant/plants by negatively affecting a variety of physiological and biochemical reactions. We checked the effects of methanolic extracts (allelochemical extracts) of Phytolacca latbenia (Moq.) H. Walter on antioxidant enzyme activities such as peroxidases (PODs), super oxide dismutases (SODs) and catalase (CAT) and on total protein contents (TPC), cellular injury (CI), and malondialdehyde (MDA) in the germinating seeds of Brassica napus L. (dicot) and Triticum aestivum L. (monocot). Both the crude methanolic extract root (CMER) and crude methanolic extract aerial (CMEA) of P. latbenia at 10000 ppm significantly reduced the POD activity in both the test seeds. The activity of SODs was significantly decreased by both CMER and CMEA in B. napus germinating seeds. A linear increase in the activity of CAT, CI, and MDA contents was found in both the test seeds with the increasing concentrations of CMEA and CMER, while TPC of the germinating seeds was found decreased. It is inferred that both the CMEA and CMER inhibited/delayed the seed germination, reduced the seedling growth by affecting a variety of biochemical and physiological attributes, and also caused cellular membrane injury in the germinating seeds of both the monocot and dicot seeds.